2011
DOI: 10.1371/journal.pone.0018037
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Handling in Human Induced Pluripotent Stem Cell Derived Cardiomyocytes

Abstract: BackgroundThe ability to establish human induced pluripotent stem cells (hiPSCs) by reprogramming of adult fibroblasts and to coax their differentiation into cardiomyocytes opens unique opportunities for cardiovascular regenerative and personalized medicine. In the current study, we investigated the Ca2+-handling properties of hiPSCs derived-cardiomyocytes (hiPSC-CMs).Methodology/Principal FindingsRT-PCR and immunocytochemistry experiments identified the expression of key Ca2+-handling proteins. Detailed laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
167
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 44 publications
21
167
0
2
Order By: Relevance
“…In the previous report, nifedipine at 1000 nM stopped contraction of hiPS-CMs at day 60. 27 Several reports have demonstrated that hiPS-CMs at day 20 to 40 of differentiation have electrophysiological properties and respond to ion channel blockers. [12][13][14] In the present study, electrophysiological responses to ion channel blockers in d30CMs were similar to those in d60CMs and d90CMs, although the sensitivity to the calcium channel blocker was weaker.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous report, nifedipine at 1000 nM stopped contraction of hiPS-CMs at day 60. 27 Several reports have demonstrated that hiPS-CMs at day 20 to 40 of differentiation have electrophysiological properties and respond to ion channel blockers. [12][13][14] In the present study, electrophysiological responses to ion channel blockers in d30CMs were similar to those in d60CMs and d90CMs, although the sensitivity to the calcium channel blocker was weaker.…”
Section: Discussionmentioning
confidence: 99%
“…The hiPSCs were established by retroviral delivery of Oct4, Sox-2, and Klf-4 followed by valproic acid treatment as described. 11,16 Several ARVC-hiPSC clones, which were positively stained with vital Tra-I-60 staining, were selected and expanded. Undifferentiated hiPSC colonies were cultured on mouse embryonic fibroblasts as previously described.…”
Section: Establishment and CM Differentiation Of The Arvc-hipscsmentioning
confidence: 99%
“…Therefore, interpretation of data regarding cardiomyogenesis efficiency and subtype identity must not only consider the presence and quantity of reference marker levels, but must consider the developmental stage(s) to which the timepoints of differentiation that are analyzed correspond. This is especially important considering that the maturation stage of cardiomyogenic cells generated by in vitro differentiation of hPSCs resembles most closely those of embryonic/fetal development [21][22][23][24][25] . Thus, relying on a marker's spatial expression in the postnatal heart may not be appropriate for the assessment of hPSCderived cells, at least in some cases.…”
Section: Introductionmentioning
confidence: 99%